PENGARUH APLIKASI GOOGLE CLASSROOM TERHADAP MINAT BELAJAR SISWA SMA/SMK - Sri Arum; Yoga Budi Bhakti (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2020)
This study aims to determine the effect of alternative learning media Google Classroom on student learning interest as a learning media bridge in the co-19 pandemic situation. Is this application can increase student interest in learning. It is feared that with the spread of Covid-19 student interest in learning will decline and carry out boring distance learning activities because the assignment and provision of material is not varied and effective. From the results of the survey by giving a questionnaire statement via google form conducted on high school students (high school) or equivalent to determine student responses to learning media. The results of student responses obtained an average value of agreeable presentation of 63.9% and 36.1% disagree, including the category of "strong". This shows that the response of students is positive towards learning media. Students find it helpful to use Google Classroom learning media because they can study wherever and whenever. This Google classroom learning media can also be accessed on a variety of communication tools both computers, laptops, tablets, and smartphones. So that students more easily do learning with the teacher during this co-19 pandemic